CRITERIA FOR THE FORMATION OF READINESS TO PROFESSIONAL ACTIVITY OF ENGINEERS BASED ON 3D-MODELING - Kyrychenko, Olexandr S. (Educological discourse, 2017)
In this article, the author singles out the criteria for the formation of readiness to professional activity of higher education engineers based on 3D-modeling. A review of the latest publications about the formation of criteria for readiness for professional activity and about modeling and modeling of the training of engineers. In addition, pedagogical aspects of 3D modeling technology are considered. The pedagogical feasibility of using 3D-modeling in the professional training of future engineers is revealed. It consists in identifying of interested educational applicants who showed interest in knowledge, helping them to obtain a steady interest in 3D-models construction, for example, using the 3D-tools of automated design tools or using 3D-printing technologies. Terminological terms "criterion" and "indicator" are analyzed, taking into account various approaches to interpretation, including pedagogical interpretation, of the term "criterion". It is noted that the term "criterion" is broader in its meaning than the term "indicator" and is defined as a measurement, that is, the rule that should be used in diagnosing. Four main criteria for the formation of readiness have been proposed: motivational, integration, activity and creative. For each selected criterion, the indicators of its manifestation are specified. Based on the identified criteria and indicators of their manifestation, the following levels of readiness are marked: low, medium, sufficient and high. Moving at marked levels of the formation of engineer’s readiness based on 3D-modeling technology. It can provide a better level of training of engineers.